Effect of impregnation with polyethylene glycols (PEGs) of different end groups on gas separation performance of cross-linked polyethylene oxide (PEO) membranes - Shanshan Ji; Teng Wang; Lu Guan; Chengyang Zhao; Shuai Quan; Xuewei Dong; Xianzhi Zhang; Fandi Meng; Zhicheng Tian (PLoS ONE, 2026)
Polymer membranes offer an extremely attractive solution for achieving sustainable carbon dioxide capture and have the potential for large-scale application. The authors prepared almost amorphous polyethylene oxide separation membranes through cross-linking methods, with a CO 2 /H 2 separation coefficient of 7.9. However, there is still the drawback of low CO 2 permeability. To improve the performance of the cross-linked membranes, this paper utilized the swelling property of the cross-linked membranes and immersed them with different end groups of PEG aqueous solutions. The effects of different end groups on the gas separation performance of the cross-linked membranes were investigated. The results showed that after being impregnated with different end group PEG, the gas permeabilities of the cross-linked membranes increased. When using a polyethylene glycol with a molecular weight of 250 g/mol for impregnation, a 47.0wt.% increase in weight was observed, and the gas permeability and CO 2 /H 2 separation coefficient of the cross-linked membranes increased significantly. The CO 2 permeability increased from 170 Barrer of the original membrane to 1457 Barrer, and the separation coefficient of H 2 increased from 7.9 to 13.